The Prophylactic and Therapeutic Effects of Saffron Extract and Crocin on Ethanol Withdrawal Syndrome in Mice - Maryam Shoja; Soghra Mehri; Bahareh Amin; Vahid Reza Askari; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2018)
Objectives: Ethanol withdrawal following its chronic use is a serious outcome and challenging to treatment. The chronic use of ethanol induces a progressive neuroplasticity in different reigns of brain. In this study we evaluated the effects of aqueous extract of Crocus sativus L. (saffron) and its active compound, crocin, on the withdrawal behavior induced after repeated administration of ethanol, in two regimens of prophylactic (administration of drugs concomitant with the induction of dependence) and treatment (administration of drugs during the period of ethanol withdrawal) in mice which received ethanol. Methods: Ethanol dependence was induced by oral administration of 10% v/v ethanol (2 g/kg) for 7 days. The aqueous extracts of saffron (40, 80 and 160) and crocin (10, 20 and 40 mg/kg) were administered to mice in two regimens of prophylactic (along with ethanol) and treatment (during withdrawal period). Diazepam (1 mg/kg) was used as a positive control. Six hours after discontinuation of the ethanol, seizure was evaluated by the sub-convulsive dose of pentyleneltetrazole (PTZ) (30 mg/kg). The open field test and Rota rod test were used for evaluation of locomotor activity and motor incoordination, respectively. Results: Both extracts and crocin increased the number of crossed lined in the open field test. PTZ kindling seizure was inhibited in animals received extract (80 and 160 mg/kg) in both regimens. Motor incoordination was only improved following administration of crocin. Conclusion: The aqueous extract of saffron and crocin can be considered as safe agents and reliable alternative to diazepam in management of ethanol withdrawal syndrome.